Implementasi Al Maslahah Al Mursalah dalam Fatwa Politik Yusuf Qardhawi - Mohamad Ramadan Habibi (Menara Tebuireng, 2017)
Politics is a dynamic discussion which follows the development and needs period of time. The reality needs to be addressed seriously by scholars of sharia to determine dhowabit that political activity is not out of order. Yusuf al Qaradhawi one of scholar who has conducted a study of political Islam. This study used qualitative methods of analysis. The data that has been done by the author showed of the fatwa political exclusion analysis showed that his fatwa inseparable from the concept of al Maslahah al Mursalah